Important Elements in Consumer’s Decision-Making Process - Sandu, Mihaela Cornelia (Calitatea Vieții, 2014)
Consumer’s decision-making process is very complex and summarizes a number of stages, from awareness of the need to search the information, evaluation, selection and purchase the product, and ultimately to his re-election if the consumer is satisfied. At the base of this process are a number of personal factors, such as age or gender, social factors, such as education or social class, psychological factors, such as motivation, perception, learning and attitude. Another extremely important element in consumer’s decision-making process is the corporate reputation which ensures the products or services quality. In this paper I will talk about all those important elements in consumer’s decision making, coming up with studies and examples in each case.